No detrimental effects of desalination waste on temperate fish assemblages. (13th December 2020) - Whitmarsh, Sasha K; Barbara, Greg M; Brook, James; Colella, Dimitri; Fairweather, Peter G; Kildea, Tim; Huveneers, Charlie
Abstract: Water resources are becoming increasingly scarce due to population growth and global changes in weather patterns. Desalination plants that extract freshwater from brackish or seawater are already being used worldwide, with many new plants being developed and built. The waste product from the extraction processes has an elevated salt concentration and can potentially cause substantial impacts to local marine flora and fauna. The present study assesses the impact of saline waste from a 100 GL/year desalination plant on southern Australian temperate fish assemblages, using baited remote underwater video. The study compared four reference sites to the impact site (desalination outfall) and found no evidence that the saline waste was having a detrimental effect on fish assemblages in proximity to the outfall, with species diversity and abundance comparable to those observed at reference sites. However, species diversity and abundance varied across geographical location, protection from fishing pressure, and reef type. Our study is one of the few assessing the ecological impacts of saline waste discharged from a large desalination plant and shows no decrease in fish diversity or abundance, which is the response typically associated with the negative impacts of anthropogenic activities on fish assemblages.